Answer:
x = 0
Step-by-step explanation:
24 - (3x - 9) - 6 = -2(4x - 10) + 5x + 7
solve the brackets by using the distribute property:
1(3x - 9) = 3x - 9
-2(2x - 10) = -8x + 20
rewrite the equation:
24 - 3x - 9 - 6 = -8x + 20 + 5x + 7
combine like therms:
27 - 3x = -3x + 27
subtract 27 from both sides:
27 - 3x - 27 = -3x + 27 - 27
- 3x = -3x
add x to both sides of the equation:
-3x + 3x = -3x + 3x
x = x or 0 = 0
to check, substitute 0 for x
24 - (3(0) - 9) - 6 = -2(4(0) - 10) + 5(0) + 7
anything times 0 is 0
24 - (0 - 9) - 6 = -2(0 - 10) + 0 + 7
solve:
24 + 9 - 6 = 0 + 20 + 0 + 7
27 = 27